2001
DOI: 10.1039/b102291c
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective [2 + 3] cycloaddition of nitrones to platinum-bound organonitriles. First enantioselective synthesis of Δ4-1,2,4-oxadiazolines†

Abstract: under mild conditions to give the corresponding ∆ 4 -1,2,4-oxadiazoline complexes cis-[PtCl 2 (R 3 MeSO)-{N᎐ ᎐ C(Ph)-ON(R 2 )-CH(R 1 )}] in 68-83% yield. In this reaction, the chiral sulfoxide in cis-[PtCl 2 (PhMeSO)(PhCN)] induces stereoselective formation of the coordinated ∆ 4 -1,2,4-oxadiazoline leading to mixtures of diastereomeric platinum complexes with a d.e. of 30-60%, which can be enhanced to >90% by fractional crystallization. The major diastereoisomer of [PtCl 2 (PhMeSO){N᎐ ᎐ C(Ph)-ON(Me)-C(H)Ph}] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…In oxygen-deficient cancer tissues this could offer an additional reaction pathway that takes place in cancer cells but less so in normal cells. It has also been shown that the synthetic strategy can be extended to analogous Pt(IV) compounds 12 and Pt(II) compounds bearing other ligands such as sulfoxides, 13 so there is future scope for further optimization of the new lead structure.…”
Section: Scheme 1 Platinum Compounds Currently Used In Cancer Therapymentioning
confidence: 99%
“…In oxygen-deficient cancer tissues this could offer an additional reaction pathway that takes place in cancer cells but less so in normal cells. It has also been shown that the synthetic strategy can be extended to analogous Pt(IV) compounds 12 and Pt(II) compounds bearing other ligands such as sulfoxides, 13 so there is future scope for further optimization of the new lead structure.…”
Section: Scheme 1 Platinum Compounds Currently Used In Cancer Therapymentioning
confidence: 99%
“…In the former case, the product was obtained as the racemate R C /S C ; in the latter case, as a mixture enriched in the S C stereomer (ee 70%) (see Scheme 14,compound 42). 82 The sequence of these re actions demonstrates the possibility of the stereoselective synthesis of chiral 2,3 dihydro 1,2,4 oxadiazoles through asymmetric induction of the starting platinum complex.…”
Section: Scheme 14mentioning
confidence: 97%
“…The steric properties of ligands in cis/trans positions can influence the stereoselectivity of the cycloaddition to coordinated nitrile. 82 For example, the cycloaddition reaction of nitrones to nitriles leads to the formation of a new chiral center at the carbon atom in the N-C*HR-N group (see Scheme 7). In the case of the trans arranged nitrile ligands in the platinum com plexes [PtCl n (RCN) 2 ] (n = 2 or 4), the coordinated 2,3 dihydro 1,2,4 oxadiazole molecule generated in the first step of the cycloaddition has no effect on the stereoconfiguration of the heterocycle formed in the sec ond step due to a large distance between the ligands, and the diastereomers are formed in a ratio of 1 : 1.…”
Section: Scheme 12mentioning
confidence: 99%
“…The metal centered complex allows the cycloaddition reaction between a non-activated nitrile (e.g. acetonitrile) and a nitrone to take place at 25 °C in 4-6 h to give, after displacement of the ligand from the metal center, the desired ∆ 4 -1,2,4-oxadiazoline in 70-90% yields [58][59][60]. This technology has also been used in conjunction with microwave irradiation [61,62].…”
Section: Oxadiazolinesmentioning
confidence: 99%